(untitled) (Journal of Tourism and Himalayan Adventures, 2019)
Mountaineering is an adventure tourism that has a significant economic contribution to Nepal. The mountain environment, especially the high altitude (>3000m) areas where major mountaineering activities happen, is considered to be highly impacted by current and emerging issues of climate change through different types of natural hazards. Climate change has direct and indirect impacts on the mountain environment. The glaciers are shrinking (nearly by 15% in the last half a century), and the glacial lakes are increasing (25% from 1970s-2017). The number of snow and rock avalanches are also increasing with the increase in intensities of the one-day rainfalls and increasing temperature. The rock falls, avalanches, GLOFs, and permafrost degradations are the potential threats for the mountaineering activities that can destroy the infrastructures, trekking trails, and resulting the demise of mountain climbers. The unpredictability of weather has cost a lot of lives of tourists. We underline a need of effective planning and perspectives for upscaling the mountaineering business with consideration of climate change.